EVALUASI PENGGUNAAN OBAT UNTUK BEBERAPA PENYAKIT PADA PASIEN RAWAT JALAN DI RSUD CILACAP - , DYAH AYU WIDOWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background:Rational use of medicines affects the quality of treatment, care, and treatment costs. Drug use evaluation isextemely important, and drug use evaluation criteria are statements that define correct drug usage with regard to various components. Rational use of medicines can be identified with prescription drugs . Indicators used to measure the rational use of drugs was WHO indicator (1993 ) . Various studies shown that the use of drugs was not fully optimal and rational state. To ensure the quality oftherapy, standart treatment guideline, hospital formulary, and the essensial medicines list towards rational use of medicine. From the background , it is necessary to do research on drug use with standard treatment guidelines, hospital formulary, and the essensial medicines list in several disease patients in outpatient departement hospital Cilacap . Aim:This study aims to determine drug use with standard treatment guidelines hospital, hospital formulary, and the essensial medicines list in several diseases outpatient departement in hospital Cilacap. Methods:This research was a descriptive analytical research design with case study model and retrospective data, using qualitative and quantitative data. Qualitative data were obtained by in depth interview while quantitative data were gathered from document observation. Results: For Pulmonary Tuberculosis, average number of drugs per encounter was 3.18 items, percentage of therapeutic guideline was 71.3 %, percentage of the essensial medicines list was 71.51%, percentage of hospital formulary was 100%. For hypertension, average number of drugs per encounter was 2.26 items, percentage of therapeutic guideline was 73.05 %, percentage of the essensial medicines list was 87.27%, percentage of hospital formulary was 82.93%. Conclusion:Drug use in Pulmonary Tuberculosis ang hypertension disease wa not fully compliance with standart treatment guidelines, hospital formulary, and the essesial medicine list.